Silicon-based negative electrode material and preparation method and application thereof

By doping metal elements and covering carbon layers in the silicon-based anode material, the problem of volume expansion and insufficient conductivity of the silicon-based anode material during charging and discharging is solved, and specific capacity improvement and cycling performance improvement is achieved. It is suitable for lithium-ion batteries with high energy density and high safety.

CN119674027APending Publication Date: 2025-03-21ZHONGYU PEGASUS NEW MATERIALS TECH INNOVATION CENT (ZHENGZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900048.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The silicon-based negative electrode material will produce huge volume expansion during charging and discharging, resulting in powderization of the active material, rapidly decreasing its capacity, and poor conductivity, limiting its large-scale application in lithium-ion batteries.

Method used

By doping metal elements appropriately, the silicon oxygen frame pores are increased, their micromorphology is changed, electron conductivity and lithium ion diffusion kinetics are improved, and the conductive carbon layer is coated on the surface to improve structural stability and overall conductivity.

Benefits of technology

The specific capacity improvement, conductivity enhancement, mechanical strength enhancement, cycle stability improvement and volume expansion reduction during charging and discharging of the silicon-based negative electrode material are achieved, and the energy density and cycling performance of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674027A_ABST
    Figure CN119674027A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary battery negative electrode materials, and particularly relates to a silicon-based negative electrode material and a preparation method and application thereof. The silicon-based negative electrode material comprises a silica frame main body structure, doped metal elements and a surface carbon coating layer. The method comprises the following steps: mixing a silicon-based compound, a metal oxide, a template agent and water, stirring at high temperature, roasting and activating at high temperature to obtain a precursor, and performing surface carbon coating on the precursor to obtain the silicon-based negative electrode material. The negative electrode material is applied to preparation of lithium ion batteries and sodium ion batteries. The silicon-based negative electrode material is nanoparticles, has a relatively large outer surface area and relatively high surface activity and is more beneficial to storage of lithium ions and sodium ions, meanwhile, the nanoparticles have a shorter diffusion path in size and are beneficial to diffusion of the lithium ions and the sodium ions, and the conductivity of the electrode material can be improved by doping metal elements and coating the surface with carbon. The material has zero strain characteristic, high energy density and excellent cycle performance in lithium ion batteries and sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery negative electrode materials, and in particular relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous consumption of traditional energy and the urgent need for large-scale storage, electric vehicles and portable electronic devices, the development of energy storage devices with higher energy density has become a top priority. Lithium-ion batteries are widely used in all aspects of life today due to their advantages such as no memory effect, long cycle life and green environmental protection. In recent years, lithium-ion batteries have developed rapidly in the fields of new energy vehicles and large-scale energy storage. However, as the negative electrode material of traditional commercial lithium-ion batteries, graphite has a low capacity (372mAh / g) and safety hazards of lithium dendrites, which hinder its further application. The development of high energy density and high safety lithium-ion battery negative electrode materials is the focus of the current development of lithium battery technology. Silicon-based negative electrode materials have become a strong candidate for the next generation of negative electrode materials with ultra-high theoretical specific capacity and low operating voltage, and have gradually been commercialized. However, the silicon-based negative electrode material will produce a huge volume expansion during the charging and discharging process, which will cause the active material to pulverize and lead to a rapid decrease in capacity; and in the current commercial battery manufacturing, due to its huge volume expansion, the amount of silicon-based negative electrode material added is less than 10wt%, which seriously restricts the large-scale application of single silicon in lithium-ion batteries, and the energy density of the prepared battery still cannot meet the growing requirements. Silicon is a semiconductor material with poor electrical conductivity. It is not conducive to the effective release of battery capacity at high rates, which is also one of the factors restricting its further application. Therefore, for silicon-based negative electrode materials, it is crucial to achieve low strain or even zero strain characteristics and improve conductivity. Summary of the invention

[0003] In order to solve the above technical problems, the present application provides a silicon-based negative electrode material and a secondary battery comprising the silicon-based negative electrode material, so as to improve the specific capacity and conductivity of the negative electrode material, enhance the mechanical strength, improve the cycle stability and reduce the volume expansion during the charge and discharge process, thereby improving the energy density and cycle performance of the secondary battery.

[0004] The technical solution of the present invention to solve the above technical problems is as follows:

[0005] The appropriate amount of metal element doping can increase the pores of the silicon-oxygen framework, change the microscopic morphology of the silicon-oxygen framework, and provide more defects and active sites, thereby improving the electronic conductivity and lithium ion diffusion kinetics of silicon-based materials. Combined with the carbon coating on the outer layer, the structural stability of the silicon-based negative electrode material is significantly improved, further improving the overall conductivity.

[0006] A silicon-based negative electrode material comprises a silicon-oxygen framework main structure, doped metal elements and a surface carbon coating layer, wherein the silicon-oxygen framework main structure is a three-dimensional skeleton structure formed by intersecting ten-membered ring "zigzag" channels along the a-axis direction and ten-membered ring straight channels along the b-axis direction, the pore size of the ten-membered ring "zigzag" channels along the a-axis direction is 0.50-0.56nm, and the pore size of the ten-membered ring straight channels along the b-axis direction is 0.52-0.58nm; the silicon-based negative electrode material is a nanoparticle, at least one dimension of which is between 20-500nm.

[0007] A method for preparing a silicon-based negative electrode material comprises the following steps:

[0008] S1, mixing the silicon source, the metal oxide, the amine solution, the template agent, ammonium fluoride and water to obtain a mixture, heating and stirring, and separating the solid in the product after the reaction is completed to obtain a first solid;

[0009] S2, washing, drying and calcining the first solid in S1 in sequence to obtain the second solid;

[0010] S3, adding the second solid matter and tris(hydroxymethylaminomethane) buffer solution in S2 into deionized water, and then adding a carbon source under mechanical stirring, followed by filtering and drying, and calcining at high temperature in an inert gas containing a reducing gas, to finally obtain the silicon-based negative electrode material.

[0011] Furthermore, the preparation method satisfies one or more of the following conditions A, B, C, and D:

[0012] Condition A is: the silicon source is one or more of tetraethyl orthosilicate, triethoxysilane, silica gel, and fumed nano-silica;

[0013] Condition B is: the template agent is one or more of tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium bromide;

[0014] Condition C is: the amine is one or more of triethylamine, p-phenylenediamine, triethanolamine, diethanolamine, monoethanolamine, and diisopropylamine;

[0015] Condition D is: the metal oxide is one or more of aluminum oxide, titanium dioxide, sodium oxide, potassium oxide, copper oxide, and lithium oxide.

[0016] Furthermore, the molar ratio of silicon element to metal element is 100:(0.3-2).

[0017] Furthermore, the heating and stirring temperature in step S1 is controlled at 90-200°C.

[0018] Furthermore, in step S2, the calcination temperature is 400-650°C.

[0019] Furthermore, in step S3, the mass ratio of the second solid to the carbon source is 1:(0.1-4).

[0020] The high temperature calcination in step S3 is carried out at a temperature of 500-1000° C. and for a time of 2-6 hours.

[0021] A silicon-based negative electrode material is prepared by adopting the above preparation method.

[0022] The above silicon-based negative electrode materials are used in lithium-ion batteries and sodium-ion batteries.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention provides a main structure of a silicon-oxygen framework synthesized by using a template agent. The crystal structure is composed of a zigzag channel (0.50-0.56 nm) of a ten-membered ring along the a-axis and a straight channel (0.52-0.58 nm) of a ten-membered ring along the b-axis, which cross each other to form a three-dimensional skeleton structure. The channel can accommodate lithium ions or sodium ions, avoiding the volume expansion caused by the alloy addition reaction and ensuring the stability of the structure during the cycle process.

[0025] (2) The preparation method of the silicon-based negative electrode material of the present invention adopts doping with metal elements to enlarge the pores of the silicon-oxygen framework, provide more defects and active sites, and thus help improve the electronic conductivity;

[0026] (3) The silicon-based negative electrode material of the present invention has a silicon-oxygen framework as the core and a conductive carbon layer coated on the surface thereof, wherein the pores of the silicon-oxygen framework provide storage space for lithium ions and sodium ions. In addition, the coated conductive carbon layer enhances the overall conductivity of the silicon-based negative electrode material and the stability of the electrolyte interface, effectively improving the cycle life of the silicon-based negative electrode material;

[0027] (4) The silicon-based negative electrode material of the present invention is a nanoparticle. As the particle size decreases, the ratio of the number of external atoms to the number of internal atoms increases rapidly. The nanoparticles have a larger surface area and higher surface activity. The surface has more reaction sites, which is more conducive to the storage of lithium ions and sodium ions. In addition, a smaller particle size has a shorter diffusion path, which is conducive to the diffusion of lithium ions and sodium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 X-ray diffraction image of silicon-based negative electrode material obtained in Example.

[0029] Figure 2 This is a scanning electron microscope image of the silicon-based negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0030] A silicon-based negative electrode material comprises a silicon-oxygen framework main structure, doped metal elements and a surface carbon coating layer, wherein the silicon-oxygen framework main structure is a three-dimensional skeleton structure formed by intersecting ten-membered ring "zigzag" channels along the a-axis direction and ten-membered ring straight channels along the b-axis direction, the pore size of the ten-membered ring "zigzag" channels along the a-axis direction is 0.50-0.56nm, and the pore size of the ten-membered ring straight channels along the b-axis direction is 0.52-0.58nm; the silicon-based negative electrode material is a nanoparticle, at least one dimension of which is between 20-500nm.

[0031] Furthermore, a method for preparing a silicon-based negative electrode material comprises the following steps:

[0032] S1, mixing the silicon source, the metal oxide, the amine solution, the template agent, ammonium fluoride and water to obtain a mixture, heating and stirring, and separating the solid in the product after the reaction is completed to obtain a first solid;

[0033] S2, washing, drying and calcining the first solid in S1 in sequence to obtain the second solid;

[0034] S3, adding the second solid matter and tris(hydroxymethylaminomethane) buffer solution in S2 into deionized water, and then adding a carbon source under mechanical stirring, followed by filtering and drying, and calcining at high temperature in an inert gas containing a reducing gas, to finally obtain the silicon-based negative electrode material.

[0035] Furthermore, the preparation method satisfies one or more of the following conditions A, B, C, and D:

[0036] Condition A is: the silicon source is one or more of tetraethyl orthosilicate, triethoxysilane, silica gel, and fumed nano-silica;

[0037] Condition B is: the template agent is one or more of tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium bromide;

[0038] Condition C is: the amine is one or more of triethylamine, p-phenylenediamine, triethanolamine, diethanolamine, monoethanolamine, and diisopropylamine;

[0039] Condition D is: the metal oxide is one or more of aluminum oxide, titanium dioxide, sodium oxide, potassium oxide, copper oxide, and lithium oxide.

[0040] Furthermore, the molar ratio of silicon element to metal element is 100:(0.3-2).

[0041] Furthermore, the heating and stirring temperature in step S1 is controlled at 90-200°C.

[0042] Furthermore, in step S2, the calcination temperature is 400-650°C.

[0043] Furthermore, in step S3, the mass ratio of the second solid to the carbon source is 1:(0.1-4).

[0044] Furthermore, the high temperature calcination in step S3 is carried out at a temperature of 500-1000° C. and for a time of 2-6 hours.

[0045] Furthermore, the silicon-based negative electrode material is applied to a secondary battery, wherein the secondary battery comprises a negative electrode, wherein the negative electrode comprises a negative electrode active material layer, and wherein the negative electrode active material layer comprises the silicon-based negative electrode material as claimed in claim 1.

[0046] Furthermore, the negative electrode material as claimed in claim 9 is used to prepare lithium-ion batteries and sodium-ion batteries.

[0047] A method for preparing a silicon-based negative electrode material comprises the following steps:

[0048] S1: Mix the silicon source, metal oxide and water, then add the template and stir to obtain a mixed reactant.

[0049] S2: subjecting the mixed reactant obtained in step S2 to a crystallization reaction, separating the solid in the product, and obtaining a first solid.

[0050] S3 washes, extracts, dries, and roasts the first solid obtained in step S2 to obtain a second solid.

[0051] S4: adding the second solid matter and tris(hydroxymethyl)aminomethane (Tris) buffer in step S3 into deionized water, then adding dopamine hydrochloride under mechanical stirring, followed by filtering and drying, and calcining at high temperature in an inert gas containing a reducing gas, to finally obtain the silicon-based negative electrode material.

[0052] Furthermore, in step S1, the molar ratio of the silicon source, the template, the ammonium fluoride and the water is 1: 0.01-0.2: 0.08-0.8: 20-50.

[0053] Furthermore, in step S1, the stirring time is 6h-24h and the temperature is 50-90°C.

[0054] Furthermore, in step S2, the temperature of the crystallization reaction is 90-200° C., and the time is 12-72 hours.

[0055] Furthermore, in step S2, the drying temperature is 100-150° C. and the drying time is 10-15 hours.

[0056] Furthermore, the calcination temperature in step S3 is 500-650° C. and the calcination time is 3-7 hours.

[0057] Furthermore, the calcination treatment in step S4 is carried out at a temperature of 500-1000° C. and for a time of 2-6 hours.

[0058] Embodiment 1:

[0059] Preparation of silicon-based negative electrode materials:

[0060] (1) Weigh 17.33 g of tetraethyl silicate and 0.07 g of aluminum oxide, add them to 45 ml of deionized water and stir for 1 h. Then add 2.22 g of template TPAOH and let it stand in an oven at 90 °C for 12 h. After standing, add 2.47 g of ammonium fluoride and stir at 90 °C for 12 h.

[0061] (2) The mixed solution was stirred at 160° C. for 72 h. After the reaction was completed, the obtained solid product was washed and filtered three times. The filtered product was dried in an oven at 120° C. for 12 h to obtain a first solid product.

[0062] (3) The first solid material is placed in a muffle furnace and calcined at 550° C. for 5 h to remove the TPAOH template to obtain a second solid material.

[0063] (4) The second solid substance (3) and 3 g of Tris buffer were added to deionized water, and then 3 g of dopamine hydrochloride was added under mechanical stirring, and the mixture was stirred for 12 h, then filtered and dried, and heated under Ar / H 2 The silicon-based negative electrode material is finally obtained by calcining at 700° C. in gas for 4 hours.

[0064] Preparation of lithium-ion batteries:

[0065] Preparation of negative electrode sheet: The silicon-based negative electrode material prepared above is used as the active material, Super P as the conductive agent, and PVDF as the binder. The mass ratio of active material, Super P, and PVDF is 80:10:10. The active material and Super P are fully mixed in proportion and ground evenly, and 5% PVDF N-methylpyrrolidone (NMP) solution is added in proportion and stirred for 1h. Finally, the mixture slurry is evenly coated on the copper foil, and vacuum dried at 105℃ for 12h, and punched into a circular electrode sheet with a diameter of 10mm. The loading amount of active material is about 1.0mg / cm 2 Up to 4.0mg / cm 2 .

[0066] Dissolved in 1 mol / L LiPF 6Ethylene carbonate / dimethyl carbonate (EC / DMC, volume ratio of 1:1) and a mixed solution containing 2 vol.% of vinylene carbonate (VC) were used as the electrolyte, PP / PE / PP separator was used, and lithium sheet was used as the counter electrode to assemble into a button half-cell in a glove box.

[0067] Embodiment 2:

[0068] The preparation method of the silicon-based negative electrode material is similar to that of Example 1, except that the metal oxide is replaced by copper oxide.

[0069] Embodiment 3:

[0070] The preparation method of the silicon-based negative electrode material is similar to that of Example 1, except that the template is replaced by TPABr and 5 g of triethanolamine is additionally added.

[0071] Embodiment 4:

[0072] Preparation of silicon-based negative electrode materials:

[0073] 1) Weigh 17.33 g of tetraethyl silicate and 0.07 g of aluminum oxide, add to 45 ml of deionized water and stir for 1 h, then add 2.22 g of template TPAOH and let it stand in an oven at 90 ° C for 12 h. After standing, add the prepared 2.47 g of ammonium fluoride and stir at 90 ° C for 12 h.

[0074] (2) The mixed solution was stirred at 160° C. for 72 h. After the reaction was completed, the obtained solid product was washed and filtered three times. The filtered product was dried in an oven at 120° C. for 12 h to obtain a first solid product.

[0075] (3) The first solid material is placed in a muffle furnace and calcined at 550° C. for 5 h to remove the TPAOH template to obtain a second solid material.

[0076] (4) The second solid matter of (3) and 3 g of Tris buffer solution are dispersed in 100 ml of tannic acid aqueous solution (1.8 mg / ml), and the precipitate is collected by centrifugation, washed with deionized water three times, and then dried at 80°C for 10 h. The dried solid matter is then kept at 400°C under Ar atmosphere for 2 h, and then kept at 800°C for 3 h to finally obtain the silicon-based negative electrode material.

[0077] Embodiment 5:

[0078] Preparation of silicon-based negative electrode materials:

[0079] (1) Weigh 6932 g of tetraethyl silicate and 28 g of aluminum oxide into a 50 L glass jar, then add 18 L of deionized water, then add 888 g of template TPAOH, stir at 90 ° C for 12 h, then add 988 g of prepared ammonium fluoride, and react at 90 ° C for 120 h.

[0080] (2) After the reaction is completed, the obtained solid product is washed and filtered three times, and the filtered product is dried in an oven at 120° C. for 12 h to obtain a first solid product.

[0081] (3) The first solid was placed in a muffle furnace and calcined at 550°C for 5 h to remove the TPAOH template to obtain a second solid. (4) The second solid and 1.2 kg of Tris buffer were added to deionized water, and then 1.2 kg of dopamine hydrochloride was added under mechanical stirring, stirred for 12 h, and then filtered and dried, and heated under Ar / H 2 The silicon-based negative electrode material is finally obtained by calcining at 700° C. in gas for 4 hours.

[0082] Embodiment 6:

[0083] The preparation method of the silicon-based negative electrode material is the same as that in Example 1, except that the negative electrode plates are assembled into a sodium ion battery.

[0084] Preparation of sodium ion batteries:

[0085] Preparation of negative electrode sheet: The silicon-based negative electrode material prepared above is used as the active material, Super P as the conductive agent, and PVDF as the binder. The mass ratio of active material, Super P, and PVDF is 80:10:10. The active material and Super P are fully mixed in proportion and ground evenly, and PVDF N-methylpyrrolidone (NMP) solution is added in proportion and stirred for 1h. Finally, the mixture slurry is evenly coated on the copper foil, and vacuum dried at 105℃ for 12h, and punched into a circular electrode sheet with a diameter of 10mm. The loading amount of active material is about 1.0mg / cm 2 Up to 4.0mg / cm 2 .

[0086] Dissolved in 1 mol / L NaPF 6 A button-type half-cell was assembled in a glove box using a mixture of ethylene carbonate / diethyl carbonate (EC / DEC, volume ratio of 1:1) as the electrolyte, a PP / PE / PP separator, and a sodium sheet as the counter electrode.

[0087] Embodiment 7:

[0088] The preparation method of the silicon-based negative electrode material is the same as that of Example 2, except that the negative electrode plates are assembled into a sodium ion battery.

[0089] Embodiment 8:

[0090] The preparation method of the silicon-based negative electrode material is the same as that of Example 3, except that the negative electrode plates are assembled into a sodium ion battery.

[0091] Embodiment 9:

[0092] The preparation method of the silicon-based negative electrode material is the same as that of Example 4, except that the negative electrode plates are assembled into a sodium ion battery.

[0093] Embodiment 10:

[0094] The preparation method of the silicon-based negative electrode material is the same as that of Example 5, except that the negative electrode plates are assembled into a sodium ion battery.

[0095] The preparation method of the silicon-based negative electrode material is similar to that of Example 1, except that aluminum oxide is not added.

[0096] Comparative Example 2:

[0097] The method for preparing the silicon-based negative electrode material is similar to that of Example 1, except that step (4) is removed.

[0098] Table 1 shows the electrochemical performance of lithium-ion batteries of silicon-based negative electrode materials of the embodiments and comparative examples.

[0099] Table 2 shows the electrochemical performance of the sodium ion battery of the silicon-based negative electrode material of the embodiment.

[0100]

[0101] Table 1

[0102]

[0103] Table 2

[0104] In general, the present invention belongs to the technical field of secondary battery negative electrode materials, and in particular, relates to a silicon-based negative electrode material and its preparation method and application. The silicon-based negative electrode material of the present application includes a silicon-oxygen framework main structure, doped metal elements, and a surface carbon coating layer. The method mixes a silicon-based compound, a metal oxide, a template, and water and stirs at high temperature, activates the mixture by high-temperature calcination to obtain a precursor, and then carbon-coats the precursor on the surface to obtain a silicon-based negative electrode material. The method is based on the template-induced formation of a crystalline silicon-oxygen framework during high-temperature stirring of the silicon-based compound. The crystal is composed of a zigzag channel (0.50-0.56nm) of a ten-membered ring along the a-axis direction and a straight channel (0.52-0.58nm) of a ten-membered ring along the b-axis direction, which cross each other to form a three-dimensional skeleton structure capable of storing lithium ions and sodium ions. The silicon-based negative electrode material is a nanoparticle with a large surface area and high surface activity, which is more conducive to the storage of lithium and sodium ions. At the same time, the nanoparticle size has a shorter diffusion path, which is conducive to the diffusion of lithium and sodium ions. Doping with metal elements and surface carbon coating can improve the conductivity of the electrode material. The material has zero strain characteristics, high energy density and excellent cycle performance in lithium-ion batteries and sodium-ion batteries.

[0105] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A silicon-based negative electrode material, comprising a silicon-oxygen framework main structure, a doped metal element and a surface carbon coating layer, wherein the silicon-oxygen framework main structure is a three-dimensional skeleton structure composed of a zigzag channel of a ten-membered ring along the a-axis direction and a straight channel of a ten-membered ring along the b-axis direction, the pore size of the zigzag channel of the ten-membered ring along the a-axis direction is 0.50-0.56nm, and the pore size of the straight channel of the ten-membered ring along the b-axis direction is 0.52-0.58nm; the silicon-based negative electrode material is a nanoparticle, at least one dimension of which is between 20-500nm.

2. A method for preparing a silicon-based negative electrode material, characterized in that: The following steps are involved: S1, mixing the silicon source, the metal oxide, the amine solution, the template agent, ammonium fluoride and water to obtain a mixture, heating and stirring, and separating the solid in the product after the reaction is completed to obtain a first solid; S2, washing, drying and calcining the first solid in S1 in sequence to obtain the second solid; S3, adding the second solid matter and tris(hydroxymethylaminomethane) buffer solution in S2 into deionized water, and then adding a carbon source under mechanical stirring, followed by filtering and drying, and calcining at high temperature in an inert gas containing a reducing gas, to finally obtain the silicon-based negative electrode material.

3. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: The preparation method satisfies one or more of the following conditions A, B, C, and D: Condition A is: the silicon source is one or more of tetraethyl orthosilicate, triethoxysilane, silica gel, and fumed nano-silica; Condition B is: the template agent is one or more of tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium bromide; Condition C is: the amine is one or more of triethylamine, p-phenylenediamine, triethanolamine, diethanolamine, monoethanolamine, and diisopropylamine; Condition D is: the metal oxide is one or more of aluminum oxide, titanium dioxide, sodium oxide, potassium oxide, copper oxide, and lithium oxide.

4. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: The molar ratio of silicon element to metal element is 100:(0.3-2).

5. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: In step S1, the heating and stirring temperature is controlled at 90-200°C.

6. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: The calcination temperature in step S2 is 400-650°C.

7. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: In step S3, the mass ratio of the second solid matter to the carbon source is 1:(0.1-4).

8. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: The high temperature calcination in step S3 is carried out at a temperature of 500-1000° C. and for a time of 2-6 hours.

9. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material is applied to a secondary battery. The secondary battery comprises a negative electrode. The negative electrode comprises a negative electrode active material layer. The negative electrode active material layer comprises the silicon-based negative electrode material as claimed in claim 1.

10. An application of a silicon-based negative electrode material, characterized in that: The negative electrode material as claimed in claim 9 is used to prepare lithium ion batteries and sodium ion batteries.